The Carnegie Supernova Project I : Analysis of stripped-envelope supernova light curves - Taddia, Francesco (2018)
Stripped-envelope (SE) supernovae (SNe) include H-poor (Type IIb), H-free (Type Ib), and He-free (Type Ic) events thought to be associated with the deaths of massive stars. The exact nature of their progenitors is a matter of debate with several lines of evidence pointing towards intermediate mass (Minit< 20 M⊙) stars in binary systems, while in other cases they may be linked to single massive Wolf-Rayet stars. Here we present the analysis of the light curves of 34 SE SNe published by the Carnegie Supernova Project (CSP-I) that are unparalleled in terms of photometric accuracy and wavelength range. Light-curve parameters are estimated through the fits of an analytical function and trends are searched for among the resulting fit parameters. Detailed inspection of the dataset suggests a tentative correlation between the peak absolute B-band magnitude and Δm15(B), while the post maximum light curves reveals a correlation between the late-time linear slope and Δm15. Making use of the full set of optical and near-IR photometry, combined with robust host-galaxy extinction corrections, comprehensive bolometric light curves are constructed and compared to both analytic and hydrodynamical models. This analysis finds consistent results among the two different modeling techniques and from the hydrodynamical models we obtained ejecta masses of 1.1–6.2M⊙, 56Ni masses of 0.03–0.35M⊙, and explosion energies (excluding two SNe Ic-BL) of 0.25–3.0 × 1051 erg. Our analysis indicates that adopting κ = 0.07 cm2 g-1 as the mean opacity serves to be a suitable assumption when comparing Arnett-model results to those obtained from hydrodynamical calculations. We also find that adopting He I and O I line velocities to infer the expansion velocity in He-rich and He-poor SNe, respectively, provides ejecta masses relatively similar to those obtained by using the Fe II line velocities, although the use of Fe II as a diagnostic does imply higher explosion energies. The inferred range of ejecta masses are compatible with intermediate mass (MZAMS ≤ 20M⊙) progenitor stars in binary systems for the majority of SE SNe. Furthermore, our hydrodynamical modeling of the bolometric light curves suggests a significant fraction of the sample may have experienced significant mixing of 56Ni, particularly in the case of SNe Ic.